Performance improvement of wireless ad hoc networks by cross-layer design approach - Zheng, Jialing. (2010)
In this thesis, we proposed algorithms to improve the performance of wireless ad hoc networks by cross-layer design approach. Firstly, we proposed a utility-based joint power and rate adaptive algorithm (UPRA) for wireless ad hoc networks, which can be incorporated with CSMA/CA based MAC protocols. This algorithm applies to networks where the transceivers can switch between different modulation schemes hence different and discrete data rates. This algorithm aims at tradeoff between effective transmission rate and power consumption by adjusting transmission power and rate according to the real time channel state. Effective rate is formulated as the utility while power consumption is formulated as cost. Although the UPRA works based on a noncooperative game, cooperation among users can be achieved so that the throughput of the whole network will be improved. The convergence of the algorithm has also been studied in both feasible and infeasible cases.